Health care utilization in Germany : theory, methodology, and results - Swart, Enno; von Lengerke, Thomas; Janssen, Christian (Springer New York, 2014)
It is a societal given, borne out by the facts: the higher one's social status, the better health, and the longer life expectancy. As the situation persists, an important question demands attention, namely whether health care systems contribute to the inequity. Drawing accurate conclusions requires workable theory, reliable data collection instruments, and valid analytical methods.  Using one representative country to typify the industrial world, Health Care Utilization in Germany studies its subject in terms of social determinants. This singular volume offers systematic guidelines for research into health care access based on an acclaimed  behavioral model of care utilization. Contributors focus on specific social factors, medical conditions, and sectors of care to examine why differences exist, their implications, and how care providers can better match supply with demand. And many of the book's topics, such as obesity, dementia, preventive services, and immigrant health, are of global interest. Included in the coverage: Updating a classic behavioral model of health care utilization (Andersen). Use of medical services in Germany: the statutory health insurance system. Insights from quantitative and qualitative research. The problem of repeated surveys: how comparable are their results? Gender, socio-economic status and utilization of health care. Care utilization by dementia patients living at home. Utilization of physiotherapy and self-help by patients with rheumatic diseases. Social determinants of utilization of psychotherapy, prevention, and integrated care in Germany. A volume certain to spark discussion among researchers across the community, the findings and methods in Health Care Utilization in Germany will be analyzed by medical sociologists, health psychologists, public health and behavioral medicine professionals, and epidemiologists.